Specifying quality characteristics and attributes for E-Learning sites - Covella, Guillermo Juan (2002)
Education involves a continuous process of exploration, acquisition, organization, integration and delivery of information and knowledge. In recent years, e-learning sites and applications have exponentially started to grow, being a central phenomenon for the industry and education fields. Key factors for the present and future success of these applications and organizations are, on one hand, the fulfillment of technological standards for e-learning environments, and, on the other hand, the utilization of well-defined development processes and the production of required quality. One of our current concerns is the quality assessment of e-learning sites and applications. In this paper, a taxonomy of e-learning sites and applications, and ultimately the quality requirements for the Functionality characteristic are thoroughly described, regarding an intentional audience. An evaluation case study for this domain, using the WebQEM (Quality Evaluation Methodology) strategy is being runned.